History and hate : the dimensions of anti-Semitism - Berger, David, 1943- (Jewish Publication Society, 1997)
The persistence of anti-Semitism is a phenomenon that challenges Jewish historians to make ethical judgments a part of historical analysis. This comprehensive collection meets that challenge as its authors provide fresh insight into the complexities of anti-Semitism. The eight essays included in this volume are by noted scholars, each an expert in a specific historical period--from the ancient world to the twentieth century.